2017
DOI: 10.1590/1678-4162-9214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orchiectomy of seven month old bulls on bronchoalveolar immune function

Abstract: The present study evaluated the impact that orchiectomy, a routine but painful intervention in bovine husbandry, can cause on pulmonary immunity. To identify whether orchiectomy can impair lung defense, analyses of serum cortisol concentration and of alveolar macrophage and their function (phagocytosis and respiratory burst) were evaluated. Sixteen Holstein bulls (7 mo old, 250±50kg of body weight BW) were divided in two homogeneous groups -the castrated group and the sham group -and the sample were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Du Manoir et al 2002;Bertagnon et al 2017). Thus, the results of the present study demonstrate that the IN vaccination protocol led to a reduction in oxidative capacity of bronchoalveolar cells at the pulmonary level, leaving pathogens inhaled…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…Du Manoir et al 2002;Bertagnon et al 2017). Thus, the results of the present study demonstrate that the IN vaccination protocol led to a reduction in oxidative capacity of bronchoalveolar cells at the pulmonary level, leaving pathogens inhaled…”
mentioning
confidence: 49%
“…This function is initiated by cell phagocytosis, followed by the production of reactive oxygen species (ROS), which promote the elimination of internalized pathogens (Burgos et al 2011 ; Fonteque et al 2015 ). This mechanism is important to keep the respiratory tract healthy, and if this activity is reduced, it is difficult to eliminate infectious agents, consequently increasing the chance of developing bacterial pneumonia (Du Manoir et al 2002 ; Bertagnon et al 2017 ). Thus, the results of the present study demonstrate that the IN vaccination protocol led to a reduction in oxidative capacity of bronchoalveolar cells at the pulmonary level, leaving pathogens inhaled alive in the posterior respiratory tract and making it more prone to infections during the establishment of vaccine immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies that involve research on pain levels measure the serum cortisol levels, we did not measure the levels of serum cortisol because the levels of this hormone have an individual variation (Bertagnon et al 2017). Sousa et al (2019) found an increase in the level of cortisol serum in lambs from 2 of 3 groups submitted for the same surgical procedure (castration and implantation of ruminal cannula) before the analgesic protocol reinforcing the hypothesis that cortisol is influenced by the individual response.…”
Section: Discussionmentioning
confidence: 94%
“…While quantitative/semi-quantitative methods (RR and EF) are more prone to external interference (Becker et al 2012), posture assessment is a more subjective technique that may not accurately reflect the signs of chronic pain and stress (Millman 2013). Therefore Bertagnon et al (2017) suggest that the main identifying parameters of chronic pain are weight loss and changes in health status and immunity. In this way, our measured parameters such as the V, RR, pain-related postures, and blood granulocytes of the animals, indicated the procedure was deleterious to the animals, did not prevent the acute pain or discomfort.…”
Section: Discussionmentioning
confidence: 99%